Penggunaan Metode Attained Age Normal dan Projected Unit Credit Pada Perhitungan Pembiayaan Dana Pensiun (Studi Kasus: PERUMDA Tirta sakti Kerinci) - Miranda, Dede; Arnellis, Arnellis (UNIVERSITAS NEGERI PADANG, 2022)
The problem in this study is that PERUMDA Tirta Sakti must provide guarantees to employees regarding pension funds. This study aims to calculate the amount of normal contributions, actuarial obIigations, using the AAN and PUC methods. This is applied research, and the participants are all PERUMDA Tirta Sakti Kerinci employees. Purposive sampling is the method of sampling.When compared to the Projected Unit Credit method, the findings demonstrated that the normal contribution calculated using the Attained Age Normal method increased significantly as one approached retirement age. The PUC method yields a lower amount of actuarial liabilities than the AAN method. The total amount of accumulated pension contributions has an impact on the size of theiipension benefit. The amassed annuity commitments are straight forwardly corresponding to the benefits got by the members.